2010
DOI: 10.1158/1078-0432.ccr-09-2483
|View full text |Cite
|
Sign up to set email alerts
|

The First-in-Human Study of the Hydrogen Sulfate (Hyd-Sulfate) Capsule of the MEK1/2 Inhibitor AZD6244 (ARRY-142886): A Phase I Open-Label Multicenter Trial in Patients with Advanced Cancer

Abstract: Purpose: In part A, the aim was to define the maximum tolerated dose (MTD) of the hydrogen sulfate (Hyd-Sulfate) oral capsule formulation of the mitogen-activated protein kinase kinase inhibitor AZD6244 (ARRY-142886). In part B, the aim was to compare the pharmacokinetic profile of the new Hyd-Sulfate capsule with the initial AZD6244 free-base suspension and further characterize the pharmacodynamic profile and efficacy of the new formulation.Experimental Design: In part A, 30 patients received escalating doses… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
202
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(217 citation statements)
references
References 17 publications
13
202
0
Order By: Relevance
“…10,14,[18][19][20][21][22][23] AZD6244 is a benzimidazole and selective 2nd generation MEK inhibitor with reported activity at nanomolar concentrations against purified MEK1 enzyme in preclinical solid tumor studies. [18][19][20][21][22][23] Further, AZD6244 is a noncompetitive MEK inhibitor with preclinical antitumor activity in solid tumor models including hepatocellular, colon, myeloma, thyroid, pancreatic, melanoma, and breast cancers 19,20,41 and tested clinically in phase 1 24 and phase 2 trials of advanced, refractory colorectal, melanoma, and lung cancer. [25][26][27] AZD6244 has been examined in leukemia and myeloma models, [42][43][44] however to our knowledge, has never been tested in lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,14,[18][19][20][21][22][23] AZD6244 is a benzimidazole and selective 2nd generation MEK inhibitor with reported activity at nanomolar concentrations against purified MEK1 enzyme in preclinical solid tumor studies. [18][19][20][21][22][23] Further, AZD6244 is a noncompetitive MEK inhibitor with preclinical antitumor activity in solid tumor models including hepatocellular, colon, myeloma, thyroid, pancreatic, melanoma, and breast cancers 19,20,41 and tested clinically in phase 1 24 and phase 2 trials of advanced, refractory colorectal, melanoma, and lung cancer. [25][26][27] AZD6244 has been examined in leukemia and myeloma models, [42][43][44] however to our knowledge, has never been tested in lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20][21][22][23] Furthermore, phase 1 and phase 2 solid tumor clinical trials have shown this agent to be well-tolerated and have encouraging clinical efficacy. [24][25][26][27] To our knowledge, minimal data are available on newer generation MEK inhibitors in lymphoma and moreover, this anti-MEK agent has never been examined in lymphoma. We sought to examine the mechanisms of action and cytotoxic effect of the novel 2nd generation MEK small molecule antagonist, AZD6244, in lymphoma cell lines, primary cells, and an in vivo human DLBCL xenograft model.…”
Section: Introductionmentioning
confidence: 99%
“…3,6 The approach undertaken in this study was facilitated by several developments: the discovery that genetic alterations that constitutively activate MAPK signaling can promote the dedifferentiation of thyroid-cancer cells, 12,29,30 the clinical availability of a selective MEK inhibitor, 17 and the development of iodine-124 PET-CT technology to quantify the uptake of iodine in a lesion. 18 Our results show that inhibition of the MAPK pathway with selumetinib can renew the therapeutic efficacy of radioiodine by enhancing uptake in patients with thyroid cancer that is refractory to radioiodine.…”
Section: Discussionmentioning
confidence: 99%
“…16 When BRAF activation is switched off genetically or its downstream signaling is inhibited with kinase inhibitors targeting either MAPK kinase (MEK) or BRAF, the tumors regain the ability to trap radioiodine. These preclinical observations provided the rationale for our pilot clinical study, in which patients who were found to have metastases that were refractory to radioiodine were treated with the selective, allosteric MEK 1 and MEK 2 inhibitor selumetinib (AZD6244, ARRY-142886), 17 and changes in iodine uptake were assessed by means of serial iodine-124 positron-emission tomography (PET)-computed tomography (CT). The use of iodine-124 PET-CT rather than traditional whole-body iodine-131 scintigraphy allowed for precise quantification of iodine uptake before and after selumetinib treatment in individual metastatic lesions ("lesional dosimetry") and prediction of the dose of radiation that could be delivered with iodine-131.…”
mentioning
confidence: 99%
“…The trials are now undergoing to determine the long-term effect of PLX4032, alone or in combination with other agents such as MEK inhibitor, on the survival of melanoma patients [121,122] . In regard with this, the clinical responses have also been observed in a phase II study with orally active and highly selective inhibitor of MEK1/2, AZD6244 (ARRY-142886) or temozolomide performed with 200 patients with advanced melanoma harboring B-Raf E600V mutation [123,124] . On the other hand, it has also been reported that the melanoma patients harboring the activating mutations in the KIT receptor exhibited a partial or complete response to imatinib mesylate [33] .…”
Section: Molecular Targeting Strategiesmentioning
confidence: 99%